Asorted dishes in army rations - Mat Hashim, Dzulkifly; Hassan, Mohd Ali; Abdul Rahman, Russly (1985)
The requirements for army rations are manifold and are well established, The food is prepared under strict hygienic conditions and high nutritional standards are maintained. Unfortunately due to eating habits, the question of variety becomes a predominant problem. During long field operations, the soldiers get bored eating the same dish and some indeed brought separate dishes from home and leave the army rations behind. This paper attempts to propose a choice of different dishes in each food pack supplied to the soldiers. Four basic dishes are suggested consisting of meat, chicken, fish and vegetables, each separately packed in brine or vegetable oil. Different pre-cooked powdered products packed separately in the form of stocks (akin to the 'oxo Cube') are included in the pack. These stocks can be labelled as "curry", "soup", "masak Lemak'", "asam pedas" and so on. As such the soldier can use his own discretion depending upon his taste to select whethe he would like meat curry chicken soup, "ikan asam pedas" or whatever.' The possible choice or combination of dishes is thus increased manifold. As to the feasibility of producing these different stocks, research has shown that coconut milk (santan) powder and.tamarind (asam jawa) powder could be produced and are quite stable under normal storage conlditions, indicating that this proposal could be carried out. Adjustments for different ethnic and regional variations 'could be made in thei menu. On the whoLe, it will give a better deal for our soldiers